DEVELOPING A SUSTAINABLE DESIGN TOOLKIT FOR WOOL PRODUCTS - Chen Li; Apisak Sindhuphak (Veredas do Direito Direito Ambiental e Desenvolvimento Sustentável, 2025)
This study develops a sustainable design toolkit for the wool industry to provide a systematic framework that reduces the environmental impact of wool products. Based on lifecycle thinking and circular design principles, the framework integrates global sustainability standards with industry practices across the product lifecycle, from material sourcing to end-of-life management. Using qualitative analysis, the toolkit is structured into four modules: material selection, design guidelines, production practices, and end-of-life management. Case studies and literature review were conducted to capture industry needs and synthesize existing research. The findings highlight a strong demand for the toolkit, with positive feedback from academia and supply chain partners. The toolkit consolidates fragmented standards, offering a practical and adaptable resource that will continue to evolve. This research contributes both theoretically and practically by equipping practitioners with tools to strengthen the wool industry and support the transition of the fashion and textile sector toward sustainability and circularity. It fills a gap in sustainable wool design by providing a unified framework that connects research, standards, and best practices.
Keywords: Metallurgy and Material Forming; Textile materials and evaluations; Metal Forming Simulation Techniques